Machine Learning and Embedded Computing in Advanced Driver Assistance Systems (ADAS) - Tang, Bo (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This book contains the latest research on machine learning and embedded computing in advanced driver assistance systems (ADAS). It encompasses research in detection, tracking, LiDAR